The Requirements of the Tourism Labour Market for Sustainable Growth and Skills Development - Petrovič, František; Bieliková, Hana; Beták, Norbert; Sofer, Michael; Králik, Roman (Journal of Education Culture and Society, 2025)
Aim. Aim of the article is to identify the most important expectations of professional practice in terms of professional skills that can be promoted into tourism education programs focused on education of future tourism professionals. Methods. To find out the differences between the expectations of tourism service providers towards graduates of tourism study programmes and the actual knowledge and abilities of graduates of the programs we performed an IPA analysis (Importance-Performance Analysis). Results. We found out that for example educational programmes need to pay more attention to soft skills like critical thinking as well as to teaching students to have a more proactive approach. It is also important to have subjects that enhance work and time flexibility and customer orientation. Conclusion. The article provides valuable insights for policymakers, educators, and industry stakeholders by identifying key areas for improvement, such as the emphasis on soft skills (e.g., critical thinking, proactive approaches, and customer orientation) and essential hard skills (e.g., online marketing and content development). Additionally, it offers a strategic perspective on sustainable workforce development in Slovakia’s tourism sector, contributing to a broader discourse on education reform and economic growth within the industry. Cognitive valueThe cognitive value of this article lies in its analysis of the alignment between tourism education programs and the evolving needs of the tourism labour market. By employing an Importance-Performance Analysis (IPA), it highlights the gap between the skills tourism graduates acquire and the expectations of employers.